Boss Babes and Predatory Optimism: Neoliberalism, Multi-level Marketing Schemes, and Gender. Issue 2 (3rd April 2021) - Wrenn, Mary V.; Waller, William
Abstract: Capitalism always depends on relentless sales efforts to battle against its endemic tendency toward a lack of effective demand. Multi-level marketing schemes (MLMs), which offer individuals the "opportunity" to earn income by becoming independent direct-to-consumer salespeople, emphasize and epitomize the optimism, meritocracy, and work ethic particular to our current stage of capitalism—neoliberalism. This research focuses on the co-evolution of multi-level marketing schemes and neoliberalism with a specific focus on their predation on women through "#BossBabe" rhetoric. Multi-level marketing schemes emerge from the tradition of traveling salesmen in the early twentieth century. Prior to WWII, women composed the minority of the door-to-door salesforce, their market primarily restricted to beauty products. After WWII, the number of women involved rose until women took over the majority of direct selling. Fed by the ideological imperatives of neoliberalism, growth of MLMs have increased dramatically since the 1980s, and exploded in the age of social media. Multi-level marketing schemes reinforce neoliberalism and exploit existing gender divides through faux-feminist rhetoric about female empowerment.